PENGARUH SENAM LANSIA TERHADAP KEBUGARAN KARDIORESPIRASI PADA LANSIA - Dany Pramono Putra (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 2019)
Background: As people get older, the condition ofcardiorespiratory fitness will decrease.Cardiorespiratory fitness is the ability of the heart,lungs, and blood vessels to take oxygen and thendistribute it to the tissues during rest and exercise.The cardiorespiratory fitness can be measured bydetermining VOmax. Low impact physical exercisesuch as gymnastics can help improvecardiorespiratory fitness and reduce the risk ofcardiovascular disease in the elderly. Elderlygymnastics is a mild exercise that is easy to do andnot burdensome if applied to the elderly. Objective:This study was conducted to determine the effect ofelderly gymnastics on cardiorespiratory fitness inthe elderly. Method: This study used quasiexperimental method with pre-test and post-test ofone group design. The sample was 17 elderly withnon-probability sampling. The sample was dividedinto 1 group i.e. the group given elderly gymnasticpractice done 3 times a week for 4 weeks. Thestudy used a Six Minutes Walking Test (SMWT)measuring instrument that was converted into theVO22max formula to measure the cardiorespiratoryfitness. The normality test was SaphiroWilk test.Hypothesis test with paired sample t-test was usedto determine the improvement of cardiorespiratoryfitness in the treatment group. Result: Hypothesistest result in treatment group with paired sample ttest obtained p = 0,000, which means there isinfluence of elderly gymnastics towardimprovement of cardiorespiratory fitness in theelderly. Conclusion: There is an influence ofelderly gymnastics on improving cardiorespiratoryfitness in the elderly. Suggestion: Further researchis suggested using more samples, longer studytime, and different measuring instruments.